2013
DOI: 10.3329/icmj.v1i2.13550
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Perinatal Outcome of Twin Pregnancy in a Tertiary Hospital

Abstract: Ibrahim Cardiac Medical Journal 2011; 1(2): 35-39 DOI: http://dx.doi.org/10.3329/icmj.v1i2.13550

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
16
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 0 publications
10
16
4
Order By: Relevance
“…12 Garg P and Shebl ET O, Mazhar SB also reported similar risk of preterm. [13][14][15] Preterm rate in present study was 62.7% which was higher than that reported by Muthihir JT et al, Qazi G, Sultana M et al, and Akaba GO et al 11,[16][17][18] However, Rizwan N et al and in Hanumaiah et al showed higher rates of preterm delivery on their study (84% and 74% respectively). 7,19 Authors observed a 2.28-fold increased risk of hypertensive disorder in women with twin pregnancy.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…12 Garg P and Shebl ET O, Mazhar SB also reported similar risk of preterm. [13][14][15] Preterm rate in present study was 62.7% which was higher than that reported by Muthihir JT et al, Qazi G, Sultana M et al, and Akaba GO et al 11,[16][17][18] However, Rizwan N et al and in Hanumaiah et al showed higher rates of preterm delivery on their study (84% and 74% respectively). 7,19 Authors observed a 2.28-fold increased risk of hypertensive disorder in women with twin pregnancy.…”
Section: Discussioncontrasting
confidence: 56%
“…Olusanya reported 1.2-fold increased risk in twin which was slightly lower than risk observed in present pregnancy and reported by Abasiattai AM and Sultana M et al 8,17,22 The difference in the risk of antepartum haemorrhage between studies could be explained by the difference in risk factors for antepartum haemorrhage between the studies populations.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations